The Implementation of Community Language Learning (CLL) Method in Improving Skill at the First Grade of SMPN 16 Makassar - Sulviana Sulviana; St Sakinah Ridwan (Edumaspul: Jurnal Pendidikan, 2023)
The objective of the research; (1) To find out the improvement of students’s speaking skill by using Community Language Learning (CLL) method at the first grade SMPN 16 Makassar(2)To describe the teaching speaking by using Community Language Learning (CLL) method implemented at the first grade SMPN 16 Makassar. The first grade student in junior high schools are expected to be able to speak the simple utterances in English. The subject of this research was 32 students of VII.6 in SMPN 16 Makassar. The research method used was Classroom Action Research. The intruments used in this research were speaking tests and observation checklis. The result of the study showed that the students’ responses in learning speaking was good. They enjoyed the activities using Community Language learning (CLL) method in class by having a discussion, sharing, and cooperating well. It means that there is an improving of students speaking skill after being CLL method. The students’ improvement was proved by their speaking test results which increased from all test. In cycle one, all of students final scores were under 60. In the cycle one , no one of them got final score less than 60. From the cycle two, most of the students got final score more than 70. Then, the data of cycle three showed that all of the students got score more than 70. The researcher suggests the teachers to use a topic variation to make the learning process more enjoyable. Then, for the next researchers, they could use this study as a reference to do deepest research about teaching method. Finally, for the English learners, they should keep practicing speaking English every day to make their speaking skill better.